But the Irish Sea betwixt us : Ireland, colonialism, and Renaissance literature - Murphy, Andrew (Andrew D.) (Irish literature, history, and culture., 1999)
At the rise of the Tudor age, England began to form a national identity. With that sense of self came the beginnings of the colonialist notion of the ""other"""" Ireland, however, proved a most difficult other because it was so closely linked, both culturally and geographically, to England. Ireland's colonial position was especially complex because of the political, religious, and ethnic heritage it shared with England. Andrew Murphy asserts that the Irish were seen not as absolute but as ""proximate"" others. As a result, English writing about Ireland was a problematic process, since standard.